1984
DOI: 10.1111/j.1748-5827.1984.tb03416.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐operative analgesia in the dog: a comparison of morphine, buprenorphine and pentazocine

Abstract: The efficacy of buprenorphine and pentazocine in controlling pain in dogs following orthopaedic surgery was compared with that of morphine. All three analgesics provided effective pain relief with no undesirable side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
3
3

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 16 publications
(7 reference statements)
2
39
3
3
Order By: Relevance
“…Scales described in veterinary studies have been either verbal ordinal 3-to 5-point scales (with descriptors such as none, mild, moderate, severe), numerical (ordinal) rating scales (e.g., a 4-to 10-point scale), categorized numerical rating scales with ordinal ranking of individual behaviors within three to seven "categories" (e.g., 0-2 points assigned for various behaviors within each of several behavior categories such as vocalization, movement, respiratory pattern, and posture), or visual analog scales (VAS 1 ). Verbal, numerical, categorized numerical, VAS, or a combination of two or more of these scales have been used to evaluate behavior in dogs in at least six studies of OHE or castration (Firth and Haldane 1999;Lascelles et al 1997;Lemke et al 2002;Slingsby and Waterman-Pearson 2000;Slingsby et al 2001); in 13 studies of orthopedic surgery (Brodbelt et al 1997;Budsberg et al 2002;Conzemius et al 1997;Day et al 1995;Grisneaux et al 1999;Hendrix et al 1996;Lascelles et al 1994;Mbugua et al 1989;Nolan and Reid 1993;Pibarot et al 1997;Sammarco et al 1996;Taylor and Houlton 1984;Vesal et al 1996); one study of auricular surgery (Buback et al 1996); seven studies of canine thoracotomies (Conzemius et al 1994;Pascoe and Dyson 1993;Popilskis et al 1991;Stobie et al 1995;Thompson and Johnson 1991;Vainio and Ojala 1994;Walsh et al 1999); and five studies of other soft tissue and/or orthopedic surgery patients ( Holton et al 1998a,b;Mathews et al 1996Mathews et al , 2001Reid and Nolan 1991). All of these scales are characterized by reliance on subjective evaluation of behaviors whose correlation with other behavioral or physiological indic...…”
Section: Potential Advantages For Investigatorsmentioning
confidence: 99%
“…Scales described in veterinary studies have been either verbal ordinal 3-to 5-point scales (with descriptors such as none, mild, moderate, severe), numerical (ordinal) rating scales (e.g., a 4-to 10-point scale), categorized numerical rating scales with ordinal ranking of individual behaviors within three to seven "categories" (e.g., 0-2 points assigned for various behaviors within each of several behavior categories such as vocalization, movement, respiratory pattern, and posture), or visual analog scales (VAS 1 ). Verbal, numerical, categorized numerical, VAS, or a combination of two or more of these scales have been used to evaluate behavior in dogs in at least six studies of OHE or castration (Firth and Haldane 1999;Lascelles et al 1997;Lemke et al 2002;Slingsby and Waterman-Pearson 2000;Slingsby et al 2001); in 13 studies of orthopedic surgery (Brodbelt et al 1997;Budsberg et al 2002;Conzemius et al 1997;Day et al 1995;Grisneaux et al 1999;Hendrix et al 1996;Lascelles et al 1994;Mbugua et al 1989;Nolan and Reid 1993;Pibarot et al 1997;Sammarco et al 1996;Taylor and Houlton 1984;Vesal et al 1996); one study of auricular surgery (Buback et al 1996); seven studies of canine thoracotomies (Conzemius et al 1994;Pascoe and Dyson 1993;Popilskis et al 1991;Stobie et al 1995;Thompson and Johnson 1991;Vainio and Ojala 1994;Walsh et al 1999); and five studies of other soft tissue and/or orthopedic surgery patients ( Holton et al 1998a,b;Mathews et al 1996Mathews et al , 2001Reid and Nolan 1991). All of these scales are characterized by reliance on subjective evaluation of behaviors whose correlation with other behavioral or physiological indic...…”
Section: Potential Advantages For Investigatorsmentioning
confidence: 99%
“…In this study buprenorphine produced sedation, but the analgesic effect was inferior to tramadol as could be seen from the results. Taylor and Houlton (1984) also found that buprenorphine produced more sedation than morphine in dogs and considered that this could affect analgesia assessment. Whereas in general anaesthesia there is a loss of consciousness, the sedative effect of analgesics does not play as important a role in pain assessment as in animals that are awake in the post-operative period.…”
Section: Discussionmentioning
confidence: 99%
“…T a y l o r, H o u l t o n [14] also found that buprenorphine produced more sedation than morphine in dogs and considered that this affected the analgesia assessment. Whereas, in general anaesthesia, there is a loss of consciousness, the sedative effect of analgesics does not play as important a role in pain assessment like in awake animals in the post-operative period.…”
Section: Methodsmentioning
confidence: 99%